2013
DOI: 10.31445/jskm.2012.160101
|View full text |Cite
|
Sign up to set email alerts
|

Literasi Internet dan Partisipasi Politik Masyarakat Pemilih dalam Aktifitas Pemanfaatan Media Baru

Abstract: Convergence of Communications and Information Technology support the realization of the information society as planned by WSIS signatories, including Indonesia. WSIS planned the realization of ICT literacy at 50% of the world population by 2015 and 100% by 2025. This paper will present the results of research about computer literacy in rural coastal communities. The research location selection was related to an attempt to make them as part of the global information society. This study was based on positivistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…Internet literacy has many meanings. As stated by Doyle, internet literacy is the ability to use theoretical and practical knowledge in relation to the internet as a medium of communication and information management (Mudjiyanto, 2012). Internet literacy is the ability to carry out communication activities, search for information and the like through the internet to meet needs that are possible to be fulfilled only if someone is literate on the internet (Mudjiyanto, 2012).…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…Internet literacy has many meanings. As stated by Doyle, internet literacy is the ability to use theoretical and practical knowledge in relation to the internet as a medium of communication and information management (Mudjiyanto, 2012). Internet literacy is the ability to carry out communication activities, search for information and the like through the internet to meet needs that are possible to be fulfilled only if someone is literate on the internet (Mudjiyanto, 2012).…”
Section: Theoritical Frameworkmentioning
confidence: 99%
“…Political participation of people in social media was also interesting to study, considering their decisions were closely related to the results of the general elections held. The utilization of new media in attracting political participation of voters and relationship of political participation with internet literacy factor showed that many of voters who were also social media users still tend to be apathetic toward politics [8]. Nevertheless the relationship of political participation and internet literacy showed quite high [8].…”
Section: A Social Media In Democracymentioning
confidence: 99%
“…The utilization of new media in attracting political participation of voters and relationship of political participation with internet literacy factor showed that many of voters who were also social media users still tend to be apathetic toward politics [8]. Nevertheless the relationship of political participation and internet literacy showed quite high [8]. In addition, a survey conducted on 6.330 young children in Belgia [9] also showed that despite the time they spend on social media very much, they did not follow all sorts of activities and political discussions (88% of respondents never read or forwarded emails related to political contents).…”
Section: A Social Media In Democracymentioning
confidence: 99%
“…Mereka memanfaatkan internet untuk pencarian informasi, kegiatan rekreasi, komunikasi dan keperluan transaksi keuangan (Qomariyah 2009). Selain itu, media internet juga turut mempengaruhi partisipasi politik walaupun belum terlalu signifikan mengarahkan pilihan politik masyarakat (Mudjianto 2012).…”
Section: Pendahuluanunclassified